External Debt and Economic Growth in Niger: a Vector Autoregression and Variance Decomposition Analysis - Oumarou, Issoufou (Economics and Business, 2021)
In the quest for quick economic development, many Sub Saharan African (SSA) countries borrow money to finance their budget deficits and vital infrastructure. Niger has seen its external debt increase year after year without really reaching economic development. This study uses a vector autoregressive (VAR) model to investigate the relation linking external debt and economic growth in Niger and variance decomposition forecast to verify if there is any significant impact from shocks for a period of 5 years in the future. The study utilises time series yearly data provided by the World Bank for the period covering 1970–2019. The empirical results reveal no long-run relationship between economic growth, external debt and government spending in Niger. The results also indicated that, on average ceteris paribus, the past realisation of economic growth is related to an increase of 97.75 % in economic growth, while the past realisation of external debt and government spending is associated with an increase of 83.77 % and 79.70 % in external debt and government spending, respectively. The results furthermore show that economic growth has a statistically significant causal effect on government spending in the short term. One percentage increase in economic growth accounts for an increase of 35.28 % in government spending on average ceteris paribus. The variance decomposition forecast reveals that economic growth has a significant influence on predicting government spending in the future.